EMANSIPASI WANITA DALAM NOVEL JANE EYRE KARYA CHARLOTTE BRONTÐ - PATODING, TIRZA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTThis study aims at investigating a woman emancipation in a novel entitled Jane Eyre by Charlotte BrontÃ«, an English novel which was written in Victorian period in nineteenth century. This research focuses on situation of the women in a society and the action of the women in reality. The writer used a feminism theory from Betty Friedan in The Feminine Mystique.The method employed in this research is descriptive method. The novel was analysed intrinsically through the female character, including the main character and extrinsically through the portrait of English women in Victorian era. The results of this research shows that the woman emancipation is reflected through the female characters in the novel such as Jane Eyre, Bertha Mason and Hellen Burn. They are identified as women who have capability in making solution for the problems in society. Therefore, Jane Eyre who represents the woman in the novel gets her rights and appears as an independent women.Keywords: Novel, Woman Emancipation, Feminism, Victorian Era, Jane Eyre.